2022
DOI: 10.3390/su141811191
|View full text |Cite
|
Sign up to set email alerts
|

A New Multi-Criteria Approach for Sustainable Material Selection Problem

Abstract: Sustainable material selection is a crucial problem given the new demands of society and novel production strategies that consider the concepts of sustainability. Multi-criteria decision-making methods have been extensively used to help decision-makers select alternatives in different fields of knowledge. Nonetheless, these methods have been criticized due to the rank reversal problem, where the independence of the irrelevant alternative principle is violated after the initial decision problem is changed. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…In addition, better quality assessment can also increase efficiency in the frying process, resulting in more consistent and quality products (Ahmad et al, 2021). The implications of this research also include the impact on sustainability, where selecting oil from sustainable sources can reduce the environmental impact of oil production and minimize the waste of raw materials (Aires & Ferreira, 2022). In addition, research in this area supports innovation in the food industry, enabling the development of more innovative and high-quality products to meet increasingly diverse consumer needs.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, better quality assessment can also increase efficiency in the frying process, resulting in more consistent and quality products (Ahmad et al, 2021). The implications of this research also include the impact on sustainability, where selecting oil from sustainable sources can reduce the environmental impact of oil production and minimize the waste of raw materials (Aires & Ferreira, 2022). In addition, research in this area supports innovation in the food industry, enabling the development of more innovative and high-quality products to meet increasingly diverse consumer needs.…”
Section: Resultsmentioning
confidence: 95%
“…Mousavi-Nasab and Sotoudeh-Anvari identified some limitations of these algorithms, such as not presenting a solution for the RRP, limiting the assessment of rank reversal cases to the addition/removal of alternatives, and presenting new difficult-to-operationalize methods for practical applications. Moreover, all have a different degree of uncertainty that cannot be estimated because they rely on scores assigned by experts, which are subjective (based on their experience and knowledge)-see the last [31,32]. Unfortunately, none of the above algorithms are more reliable than the statistical approach proposed here, given that the experts have their opinions that cannot be objectively measured.…”
Section: Statistical Comparison Of the Importance Given To The Criter...mentioning
confidence: 99%
“…The results showed that Polysulfone material was the best choice for solar thermal applications. Aires & Ferreira 84 developed a decision-making framework for selecting the most suitable thermal insulation material for enhancing energy efficiency, by integrating Fuzzy BWM, CRITIC, and Mixed Aggregation by Comprehensive Normalization Technique (MACONT). Among the considered alternatives, Polyisocyanurate was identified as the optimal material based on the defined criteria.…”
Section: Literature Reviewmentioning
confidence: 99%